2020
DOI: 10.20960/nh.03307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lockdown for COVID-19 on self-reported body weight gain in a sample of obese patients

Abstract: Objetivo: el objetivo de este estudio fue evaluar la prevalencia de hipovitaminosis D en los candidatos a cirugía bariátrica (CB) y su relación con factores de riesgo y los componentes del síndrome metabólico. Material y métodos: los parámetros clínicos, antropométricos y bioquímicos se midieron en 56 pacientes caucásicos incluidos en un protocolo de cirugía bariátrica entre enero y junio de 2014. Los pacientes fueron estratificados en tres grupos de acuerdo al status de vitamina D: suficiencia (≥ 40 ng/ml), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 18 publications
3
33
0
10
Order By: Relevance
“…Besides the use of telemedicine, there were a number of factors that were associated with healthier weight change trends over lockdown according to univariate analysis in our study. Those who increased weekly exercise time were more likely to lose weight overall, and this was similarly reported surveys from China [20] and Spain [2]. Respondents who had a positive change in their dietary habit score (based on consumption of sweet and salty processed snacks, fruits, vegetables and homemade food) reported weight loss, while those that had a negative change gained weight and this difference was significant.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Besides the use of telemedicine, there were a number of factors that were associated with healthier weight change trends over lockdown according to univariate analysis in our study. Those who increased weekly exercise time were more likely to lose weight overall, and this was similarly reported surveys from China [20] and Spain [2]. Respondents who had a positive change in their dietary habit score (based on consumption of sweet and salty processed snacks, fruits, vegetables and homemade food) reported weight loss, while those that had a negative change gained weight and this difference was significant.…”
Section: Discussionsupporting
confidence: 65%
“…Respondents who had a positive change in their dietary habit score (based on consumption of sweet and salty processed snacks, fruits, vegetables and homemade food) reported weight loss, while those that had a negative change gained weight and this difference was significant. A deterioration in dietary habits was associated with weight gain in surveys form around the word during quarantine, including snacking [2], night eating [21], "bingeing on food" [22], and consumption of sugary drinks, pastries and fried foods [3]. Furthermore, in our study an improved mood was associated with weight loss, and a decline in mood was associated with weight gain.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The authors found that increments in BW should be considered an alarming negative effect of lockdown, as they might lead to a higher prevalence of overweight, obesity and related health-risks [68]. In a study including only obese subjects, more than one third reported an increase in their body weight during/after lockdown [69]. This finding is consistent with enhanced unhealthy eating patterns and sedentarity, indicating that this group may find it more difficult to control BW during a lockdown.…”
Section: Obesity and Covid-19: An Additional Risk Factor With Nutritional Implicationsmentioning
confidence: 83%
“…Another survey study has found a mean of 1.5 kg increase after one month of the lockdown period, self-reported anxiety and depression found a risk factor for weight gain [ 8 ]. Also, another recent study reported weight gain after lockdown beginning among obese people which was attributed to snacking habit [ 9 ]. Therefore, we might come closer to a common opinion about weight gain after the lockdown period.…”
Section: Discussionmentioning
confidence: 99%